Immunological Changes in Secondary Sjogran Syndrome (Comparative Study) - Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon (ELSEVIER, 2015)
Objective This study was designed to evaluate the immunological changes and its existence for early diagnosis and proper management of disease.